The art of 3D computer animation and effects - Kerlow, Isaac Victor 1958- (John Wiley, 2004)
An insightful, up-to-date look at creating in the digital environment In a practical, easy-to-understand format, The Art of 3-D Computer Animation and Effects covers every aspect of creating and outputting fully rendered three-dimensional computer still images or animations, including visual effects for live action. Along with helpful insights into the newest techniques available in the latest software programs and hardware, this new edition provides solid conceptual and critical basics through a combination of technical explanations and creative techniques. Creative vision can be brought to life on the screen through an easy-to-understand, step-by-step approach supported by full-color sample work by such leading companies as Pixar Animation Studios, Square, DreamWorks SKG, Fox, Disney, and many independent artists and studios. Isaac Victor Kerlow (Los Angeles, CA) is Director of Digital Production at the Walt Disney Company and a longtime active member of SIGGRAPH and the Visual Effects Society.